2021
DOI: 10.3389/fimmu.2021.729602
|View full text |Cite
|
Sign up to set email alerts
|

Description and Analysis of a Novel Subtype of the Anti-Synthetase Syndrome Characterized by Frequent Attacks of Fever and Systemic Inflammation in a Single-Center Cohort Study

Abstract: ObjectivesThe aim of this study was to investigate anti-synthetase syndrome (ASyS) patients who presented with recurrent episodes of fever and systemic inflammation.MethodsA retrospective cohort of Chinese ASyS patients (n=126) in our center (between January 2013 and January 2020) was included. Patients presenting with concomitant autoimmune rheumatic diseases or malignancies were subsequently excluded. The number of non-infectious fever attacks and attack frequency were recorded and calculated. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…4,5 As shown by both our case series and SLR, these manifestations are prominent features of AS, and they identify a difficult-to-treat disease phenotype that may not even respond to RTX. 3 Hence, the encouraging findings of our study are in line with the plausible pathogenic role of IL-1 in AS. Further, patients featuring biochemical (ie, increased acute-phase reactants) and clinical (ie, fever, myocarditis, and interstitial lung disease) signs of prominent inflammation possibly represent a disease subset that could benefit the most from this approach.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…4,5 As shown by both our case series and SLR, these manifestations are prominent features of AS, and they identify a difficult-to-treat disease phenotype that may not even respond to RTX. 3 Hence, the encouraging findings of our study are in line with the plausible pathogenic role of IL-1 in AS. Further, patients featuring biochemical (ie, increased acute-phase reactants) and clinical (ie, fever, myocarditis, and interstitial lung disease) signs of prominent inflammation possibly represent a disease subset that could benefit the most from this approach.…”
supporting
confidence: 83%
“…2 Further, this therapy may not effectively induce remission in some patients with AS. 3 Hence, alternative drugs for patients with refractory AS are necessary. Interleukin (IL)-1 blockade with anakinra might represent a suitable option due to its potent antiinflammatory properties and favorable safety profile.…”
mentioning
confidence: 99%
“…Patients with two or more non-infectious fever attacks and within the upper three quartiles of attack frequency were defined as the high-inflammation ASS subgroup (78). These patients had an average of 1.12 attacks/patient-year and were most commonly anti-Jo1 or anti-PL7-positive (78).…”
Section: Antisynthetase Syndromementioning
confidence: 99%
“…Patients with two or more non-infectious fever attacks and within the upper three quartiles of attack frequency were defined as the high-inflammation ASS subgroup (78). These patients had an average of 1.12 attacks/patient-year and were most commonly anti-Jo1 or anti-PL7-positive (78). Compared to the low-inflammation ASS group, defined by at most a single attack and a frequency lower than 0.5 attacks/patient-year, the high-inflammation ASS group had a higher occurrence of fever and RP-ILD as the disease presentation (78).…”
Section: Antisynthetase Syndromementioning
confidence: 99%
“…Fever when present should prompt investigation for infection, although the reported prevalence in ASyS ranges from 21 to 66% ( 23 , 71 ). A Chinese cohort study identified more pyrexial episodes with acute phase response in anti-PL7 (50%) and anti-Jo1 (30%) positive cases, with a more inflammatory phenotype predictive of rapidly progressive ILD (RP-ILD) ( 72 ). The large 2014 meta-analysis demonstrated more fever in non-anti-Jo1 patients as opposed to anti-Jo1 positive patients ( 18 ).…”
Section: Fevermentioning
confidence: 99%